219k views
5 votes
I need help with maths, if f(x) = 2x+1 find a) f(0)b) f(-3)c) f(2x+1)

I need help with maths, if f(x) = 2x+1 find a) f(0)b) f(-3)c) f(2x+1)-example-1
User Etang
by
4.7k points

1 Answer

4 votes

a) Replace x by 0 and simplify:

f(0) = 2(0) + 1 = 0 + 1 = 1

Hence, f(0) = 1

b) Replace x by -3 and simplify:

f(-3) = 2(-3) + 1 = -6 + 1 = -5

Hence, f(-3) = -5

c) Replace x by 2x+3 and simplify:

f(2x+1) = 2(2x + 1) + 1 = 4x + 2 + 1 = 4x + 3

Hence, f(2x+1) = 4x + 3

User Solomon Vimal
by
5.6k points